2016
DOI: 10.1590/01047760201622012085
|View full text |Cite
|
Sign up to set email alerts
|

Deficiência De Macro E Micronutrientes Em Mudas Maduras De Khaya Ivorensis Estudadas Em Viveiro

Abstract: DEFICIÊNCIA DE MACRO E MICRONUTRIENTES EM MUDAS MADURAS DE KHAYA IVORENSIS ESTUDADAS EM VIVEIRORESUMO: O mogno africano (Khaya ivorensis) é uma essência florestal de alto valor e de grande potencial para substituir o mogno brasileiro (Swietenia macrophylla). Atualmente, pouco se conhece a respeito das exigências nutricionais do mogno africano. Nesse sentido, o presente trabalho teve o objetivo de avaliar o desenvolvimento e a composição mineral de plantas de K. ivorensis submetidas à omissão de macro e micronu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 7 publications
(8 reference statements)
4
11
0
13
Order By: Relevance
“…This result may be related to the low requirement of the micronutrient by the African mahogany in its initial phase of development. A similar result was observed by Corcioli et al (2016) in another African mahogany species (Khaya ivorensis A. Chev) where the omission of zinc in fertilization did not influence the plant growth in the early stages. Evaluating the growth of Australian cedar under boron and zinc supplementation, Carmo et al (2010) concluded that Zn doses did not influence plant height and diameter during the 3-month experimental period.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This result may be related to the low requirement of the micronutrient by the African mahogany in its initial phase of development. A similar result was observed by Corcioli et al (2016) in another African mahogany species (Khaya ivorensis A. Chev) where the omission of zinc in fertilization did not influence the plant growth in the early stages. Evaluating the growth of Australian cedar under boron and zinc supplementation, Carmo et al (2010) concluded that Zn doses did not influence plant height and diameter during the 3-month experimental period.…”
Section: Resultssupporting
confidence: 84%
“…In addition to macronutrients (nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, carbon, oxygen, and hydrogen), it is also necessary to consider micronutrients which, although required in small amounts, they are fundamental to the performance of main cellular metabolic functions (Corcioli et al, 2016). Thus, the adequate supply of these nutrients is a key point for plant growth and development, including for forest species.…”
mentioning
confidence: 99%
“…However, for African mahogany, reduction in precipitation period was probably the limiting factor responsible for its low performance. This is true considering PINHEIRO et al (2011) andCORCIOLI et al (2016) observation that this species needs deep soils with high fertility and average annual precipitation of 1300 to 1800mm for healthy growth.…”
Section: Resultsmentioning
confidence: 85%
“…Pesquisas de diferentes naturezas utilizando a espécie estão se iniciando no Brasil (Falesi & Baena, 1999;Gasparotto et al, 2001;Poltronieri et al, 2002;Castro et al, 2008;Gomes, 2010;Tremacoldi et al, 2013;França et al, 2016;Corcioli et al, 2016). Siqueira et al (2002), ao avaliarem o comportamento de plantios florestais utilizando 18 espécies exóticas em Sergipe constataram que o mogno africano possuiu crescimento lento quando comparado às demais espécies, não sobrevivendo às condições da baixada litorânea.…”
Section: A Origem Da Nomenclatura Mognounclassified